Culture of Asian seabass (Lates calcarifer, Bloch) in open sea floating net cages off Karwar, south India - Philipose, K. K.; Krupesha Sharma, S. R.; Loka, Jayasree; Damodaran, Divu; Narsimhulu, Sadhu; Dube, Praveen (Indian Journal of Fisheries, 2013)
Cage farming of marine finfish is an alternative to meet increasing demand for food fish. Culture of Asian seabass in open sea floating net cages made of either HDPE or GI pipes, has been successfully demonstrated off Karwar, south India. Fish were fed with chopped oilsardine. Various growth parameters like average daily growth rate (ADGR), survival rate (SR), specific growth rate (SGR) and biomass index (BI) were estimated. Mean weight and length at the end of the 150 days experimental period was 1.02 kg and 412.05 mm respectively with a SR of 68.8%. The economics of cage farming was also worked out. The need to standardise stocking densities and feeding rate has been emphasised.